665 THE UNFORSEEN MECHANISM: A CASE OF DISTRIBUTIVE SHOCK SECONDARY TO REACTIVE HAEMOPHAGOCYTIC SYNDROME LEADING TO SEVERE REVERSIBLE BIVENTRICULAR DYSFUNCTION. (15th December 2022) - Bertelli, Michele; Foa´, Alberto; Broccoli, Alessandro; Zinzani, Pier Luigi; Stefoni, Vittorio; Semprini, Franco; Nanni, Samuele; Barberini, Francesco; Corsini, Anna; Battistini, Paola; Galie´, Nazzareno
Abstract: Distributive shock comprises a variety of processes causing dysregulated vasodilation with consequent life-threatening end-organ dysfunction. While sepsis constitutes by far its most common aetiology, other pathological mechanisms with different therapeutic targets may lead to a similar haemodynamic picture. We hereby present the case of a 35-year-old male with no past cardiological history and a recent diagnosis of stage IVsB Hodgkin's lymphoma relapse 10 years after effective disease eradication with first-line chemotherapy. Shortly after a single cycle of second-line chemotherapy, the patient presented with high fever, acute chest pain and dyspnea associated with marked hypotension and sinus tachycardia. Laboratory tests revealed pancytopenia and raised inflammatory markers as well as evidence of acute kidney injury and hepatocellular damage. Urgent thoracic CT revealed no signs of pneumonia while echocardiography demonstrated severe biventricular dysfunction with 25% left ventricular ejection fraction and severe functional mitral regurgitation. Due to worsening tachypnea and desaturation the patient was intubated and transferred to our Intensive Cardiac Care Unit where urgent instatement of circulatory support with iv fluids, blood transfusions, adrenaline and intra-aortic balloon pump were performed and empirical broad-spectrum antibiotic therapy was started after performing blood cultures from peripheral and central veins. Concurrent right ventricular catheterisation demonstrated high-output cardiac failure (Qs Fick 7.89 Qp/m2, Qs thermodilution 8.0 Qp/m2) with mild increase in biventricular filling pressures and post-capillary pulmonary hypertension. Endomyocardial biopsy in turn revealed only mild subendocardial fibrosis and oedema thus excluding myocarditis as a potential cause for the severe biventricular dysfunction. Due to worsening of renal function with persistent anuria despite circulatory support the patient required continuous veno-venous haemofiltration. Notably, over the coming days no pathogen was isolated from any of the cultures with haemodynamic and respiratory parameters gradually improving, allowing for weaning from circulatory and respiratory support. On further examination of blood tests on admission, hypertriglyceridemia, raised ferritin levels and thrombin consumption were noted. These biochemical features, together with the history of Hodgkin's lymphoma relapse, recent chemotherapy, pancytopenia and splenomegaly, suggestive of natural killer cell dysfunction-related haemophagocytosis, pointed to reactive haemophagocytic syndrome as a potential aetiology of the severe distributive shock (> 99% probability on recently published "HS Score" for Reactive Haemophagocytic Syndrome). This hypothesis was further corroborated by the gradual albeit not complete regression of the severe biventricular dysfunction after haemodynamic support suggesting that this may have represented a byproduct of the patient's high-output state. Unfortunately, due to lymphoma progression with severe multiorgan involvement the patient was admitted shortly after discharge and deceased thereafter. This case provides an example of the diversity of potential disease mechanisms underlying distributive shock where biventricular dysfunction may represent a reversible albeit severe bystander rather than the true driving factor of its life-threatening haemodynamic compromise.